The Coordination of the Implementation of the Free Nutritional Meal Program in Kindergarten and Elementary Schools at the Laboratory Development of Universitas Negeri Padang - Muthalib, Hafizh; Adnan, M. Fachri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The Free Nutritious Meal Program (MBG) is a national priority initiative whose delivery at the school level involves multiple actors across organizations. This multi-actor configuration makes coordination a key determinant of service continuity, particularly during the early implementation phase. This study describes the coordination of MBG implementation at the UNP Laboratory Development Kindergarten and Primary School and identifies supporting and inhibiting factors. A qualitative descriptive approach was employed. Data were collected in January 2026 through semi-structured interviews with the head of SPPG, kindergarten and primary school principals, teachers/homeroom teachers, and parents; observations of receiving, distribution, and consumption processes; and document review (including the MoU and implementation records). Source triangulation was applied to enhance trustworthiness. Data analysis followed the stages of data reduction, data display, and conclusion drawing/verification (Miles, Huberman, & Saldaña, 2014). The findings indicate that vertical coordination within schools generally functioned effectively because the operational chain of receiving, distributing, supervising, and reporting was supported by clear role allocation. However, horizontal coordination between SPPG and schools was unstable during the early phase, particularly in communication and delivery timeliness. The study highlights the need for written cross-actor SOPs, a robust schedule-change confirmation protocol, and more systematic use of students' health-history data and feedback (e.g., leftovers) for continuous improvement.